Evaluasi Strategi Pengembangan Stakeholders dalam Penguatan Kelembagaan Pendidikan Islam - Eem Merani Destiana; Nur Puspasari; Desy Eka Citra Dewi (STIKes Ibnu Sina Ajibarang, 2025)
This study discusses the evaluation of stakeholder development strategies in strengthening Islamic educational institutions. The study was conducted qualitatively with case studies in several Islamic educational institutions. The active involvement of stakeholders, such as principals, teachers, parents, government, and the community, has proven to be very influential in strengthening educational institutions. Collaborative and participatory strategies between institutions, the community, and the government are able to improve the quality of governance and the competitiveness of Islamic educational institutions. Determining potential stakeholders is a crucial process so that the main needs and expectations can be met optimally. Implementation of modern management, consensus, and routine monitoring and evaluation are the keys to the success of the institutional strengthening strategy. The main obstacle found is the lack of synergy and communication between stakeholders, so that discussion forums and routine training are needed. Transparency and accountability in the management of institutions are also important factors in building stakeholder trust. Continuous evaluation is needed to adjust the strategy to the dynamics of the needs of institutions and the community.